Risk Factors and Birth Outcomes Associated with Adolescent Pregnancy in Tertiary Level Hospital of Chitwan - Parajuli, Sumitra; Poudyal, Jiwan Kumar; Poudel, Madhu Maya; Regmi, Kamala; Adhikari, Pratima (Journal of Bharatpur Hospital, 2025)
Background: Adolescent pregnancy is a global public health concern and a leading determinant of adverse birth outcomes. This study was conducted to assess the risk factors and immediate birth outcomes associated with adolescent pregnancy in a tertiary hospital in Chitwan.Methods: An analytical cross-sectional study was conducted among 210 post-partum mothers at the Maternity ward of Bharatpur Hospital. Mothers aged 20-35 years were designated as the reference group for comparison. A face-to-face interview was conducted to collect socio-demographic and risk factors related data and data on maternal and neonatal outcomes collected from record files. The collected data were entered and analyzed in SPSS 20 version.Results: Adolescent pregnancy was significantly associated with Janajati/Chepang ethnicity (75.2% vs. 57.1%; p